A mobile dictionary for pilgrims - Zeki, Akram M.; Alsafi, Hassen Mohammed; Nassr, R.M.; Mantoro, Teddy (2012)
The wide use of computers in all lives pushes software designers to implement a huge number of different applications in every field and the applied programs become immeasurable. Mobile dictionary application have moved to the world of multimedia and merged other services rather than classic translation. Even though millions guidelines booklets printed in different languages and distributed among pilgrims even before they depart their countries, however many pilgrims have lack of knowledge about valid procedures of pilgrimage practices. In this paper, mobile dictionary application for Hajj using three different languages is proposed to assist the pilgrim perform their Hajj easily.